2010
DOI: 10.1163/016942409x12598231567943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cell Behaviour on Atmospheric Plasma Deposited Siloxane and Fluorosiloxane Coatings

Abstract: Osteoblasts >Hepatocytes> CHO. The HEK and THP-1 inflammatory cells in contrast were not found to be sensitive to changes in water contact angle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Both of which have not been reported before. These measurements allow the reported plasma processing outcome [12][13][14][15][16][17][18][19] to be revaluated in terms of discharge power and heat transfer. Outside the nozzle the gas temperature drops towards the surface to such a degree that allows heat sensitive treatment of polymeric and composite materials and many medical applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of which have not been reported before. These measurements allow the reported plasma processing outcome [12][13][14][15][16][17][18][19] to be revaluated in terms of discharge power and heat transfer. Outside the nozzle the gas temperature drops towards the surface to such a degree that allows heat sensitive treatment of polymeric and composite materials and many medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the nozzle the gas temperature drops towards the surface to such a degree that allows heat sensitive treatment of polymeric and composite materials and many medical applications. By selecting an appropriate gap distance of 2-3 mm and 50% of the power supply setting (*5 W discharge power), Ardhaoui et al [16] has shown that the effective temperature and abundance of activated species can be actively engineered for cell adhesion. This conclusion also has relevance to the adhesive bonding issue highlighted in the introduction where high adhesive bond strength for siloxane elastomers bonded to coated steel were obtained at the more energetic smaller gap distances between the nozzle and the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements were taken one week after the coatings were deposited in order to minimise activation effects of the plasma on the silicon wafer substrate. [28] Surface energies were determined using deionised water, diodomethane and ethylene glycol. The surface energy of the deposited coatings was then calculated using the OWRK method.…”
Section: Surface Characterisationmentioning
confidence: 99%
“…This technique in which a liquid precursor is nebulized into a plasma jet has previously been used for the deposition of a range of plasma polymerised coatings such as siloxanes and fluoropolymers. [28,29] In this study the QAS precursor investigated was dimethyloctadecyl [3-trimethoxysilyl) propyl] ammoniumchloride (C 26 H 58 ClNO 3 Si), also known as ODAMO. This precursor was selected for the protein adhesion studies due to its low toxicity, which is an important consideration in the nebulisation of this precursor into a plasma at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%